Accelerating decline of wildfires in China in the 21st century - Lian, Chenqin; Xiao, Chiwei; Feng, Zhiming; Ma, Qin (Frontiers in Forests and Global Change, 2024)
Global wildfires have increased in frequency and intensity, especially in temperate regions, in the context of global warming. However, the spatiotemporal characteristics of wildfire frequency and intensity are still not well understood. Using Moderate Resolution Imaging Spectroradiometer (MODIS) Collection 6 (C6) wildfire products during 2003-2022, here, we analyzed the spatiotemporal patterns and evolutionary characteristics of the frequency and intensity of wildfires in China. The main conclusions are: (1) Over the past 20 years, the wildfire frequency and fire radiative power (FRP) have declined at rates of -1920/year (p<0.001) and -76492MW/year (p<0.001), respectively, showing a highly significant downward trend, with declines of up to 63% and 81%. (2) Wildfires in China show a single peak pattern of high incidence in winter and spring, with the most frequent in March, followed by February and April. (3) The overall spatial distribution of wildfires in China is characterized by a bimodal distribution, with more in the south and less in the north. Wildfires are most abundant but less intense in the southern region(SR), fewer but most intense in the northeastern region(NER), and significantly influenced by El Niño in the southwestern region(SWR), with significant regional differences in wildfires in China. (4) The average FRP of wildfire spots presented a decreasing trend from 47 MW/spot in 2003 to only 25 MW/spot in 2022. This may be due to more dispersed wildfires, rather than concentrated wildfires. (5) The frequency and FRP of wildfires showed an overall negative correlation with the Standardized Precipitation Evapotranspiration Index (SPEI). Drought events (negative SPEI) have a significant effect on wildfires, especially in SR. This study demonstrates the effectiveness of current fire suppression policies in China in terms of disaster prevention and mitigation, and further provides data to further explore and analyze the impact of wildfires on the regional environment.